Rediscovery of the Sri Lankan ‘house gecko’ Hemidactylus pieresii Kelaart (Reptilia: Gekkonidae) with a redescription of Hemidactylus depressus Gray - Batuwita, Sudesh; Pethiyagoda, Rohan (Zootaxa, 2012)
Hemidactylus pieresii Kelaart, a species first described from Kandy, Sri Lanka, in 1852 but not recorded since, is redescribedfrom two recently-discovered populations, one at the type locality and another in the rainforests of the island’s south-westernlowlands. It is shown to be similar to H. depressus (in the synonymy of which it has been since 1935), from which it is distin-guished by the possession of 53–58 (vs. 35–41) paravertebral tubercles, 17–19 (vs. 13–16) longitudinal rows of middorsaltubercles, possessing relatively small (vs. large) and closely (vs. widely) spaced middorsal tubercles, 1–3 (vs. no) postcloacalspurs, chocolate-brown (vs. light brown) coloration in life, and nape with distinct black longitudinal stripes (vs. without blackstripes). Hemidactylus pieresii, a member of the H. brooki group, is distinguished from all species of Hemidactylus in Sri Lankaand peninsular India by the combination of the following additional characters: maximum snout-vent length 79.2 mm; ventralscales across midbody, 32–39; dorsal scales heterogeneous; ventral scales smooth, with 3 serrae; precloacal-femoral pores17–20 on each side, separated mesially by 1–3 poreless scales; subcaudals smooth, the median row enlarged; supralabials toangle of jaws, 11 or 12; subdigital lamellae on digit IV of pes, 10 or 11; general body colour chocolate-brown; nape with dis-tinct black longitudinal stripes. The identity of H. pieresii is stabilized through the designation of a neotype. Unlike most otherspecies of Hemidactylus, H. pieresii appears to be restricted to rainforests. Hemidactylus depressus is also redecribed from freshly collected material from Sri Lanka and its syntype BMNH RR1962.190 (65.6 mm SVL) is designated lectotype.